Determination of Dimensional and Shape Parameters of CRoss-sections of Natural Torrents in Small Mountain Watersheds - Matúš Jakubis (Mendel University Press, 2021)
The aim of this article is to assess the accuracy of estimates of geometric and shape parameters in cross-sections of natural mountain torrents using the equations of regional downstream hydraulic geometry. Equations of regional hydraulic geometry were derived for 19 natural torrents of the Western Tatras in the geomorphological unit of the Tatras. The equations for the relations between the watershed area AW (km2) and the bankfull channel width inside the banks Bbf (m), channel depth Hbf (m), channel cross-section area Abf (m2) and shape characteristics of the cross-section Bbf : Hbf and Hbf : Bbf, were ascertained. At the same time, equations for the relationships between the length of the main stream LT (km) and aforementioned dimensional and shape parameters were derived. Subsequently, the measured geometric and shape parameters of the natural cross sections of torrents were compared with the calculated values. Differences between measured and calculated characteristics were found and confirmed by pairwise selection testing.